In the hurricane's eye : the troubled prospects of multinational enterprises - Vernon, Raymond, 1913-1999 (Harvard University Press, 1998)
The world's multinational enterprises face a spell of rough weather, political economist Ray Vernon argues, not only from the host countries in which they have established their subsidiaries, but also from their home countries. Such enterprises--a few thousand in number, including Microsoft, Toyota, IBM, Siemens, Samsung, and others--now generate about half of the world's industrial output and half of the world's foreign trade; so any change in the relatively benign climate in which they have operated over the past decade will create serious tensions in international economic relations. The warnings of such a change are already here. In the United States, interests such as labor are increasingly hostile to what they see as the costs and uncertainties of an open economy. In Europe, those who want to preserve the social safety net and those who feel that the net must be dismantled are increasingly at odds. In Japan, the talk of "hollowing out" takes on a new urgency as the country's "lifetime employment" practices are threatened and as public and private institutions are subjected to unaccustomed stress. The tendency of multinationals in different countries to find common cause in open markets, strong patents and trademarks, and international technical standards has been viewed as a loss of national sovereignty and a weakening of the nation-state system, producing hostile reactions in home countries. The challenge for policy makers, Vernon argues, is to bridge the quite different regimes of the multinational enterprise and the nation-state. Both have a major role to play, and yet must make basic changes in their practices and policies to accommodate each other